A STUDY ON IMPACT OF COVID-19 ON TEACHING - A STUDY ON IMPACT OF COVID-19 ON TEACHING (International Journal of Research Science and Management, 2020)
“Be the change you want to see in the world.” The petrifying and severe impact of COVID-19 has shaken the world to its core. Later, most of the Governments around the world have temporarily closed educational institutions in an attempt to stop the spread of the COVID-19 pandemic. In India, 320 million students have been affected by COVID-19 school closures, and though the government quickly recommended shifting to “online teaching.” Many of the government institutions are lacking of facilities to conduct online classes. Many teachers are to be updating them to challenge this situation otherwise leads to job threat. This paper with an objective to study out whether the faculties are ready to face challenges due to online teaching and to identify who among male and female are feeling more threat for their jobs due to online teaching.